Ent by ant - Tay, Anthea (2015)
It won’t be long before we’ve run out of food options of the future. Man enjoys pushing the limits of our resources to the point of obsolesce. The environment can no longer sustain current farming methods, and meat will no longer be a viable and economic source of protein. Trends inevitably point towards a growing number of meat eaters as more countries become developed. Soon, supply will not be able to meet demands. The solution is looking at insects as a common staple for all in the future. My project seeks to make people question the possibility of this future with insects as their first choice of food.